Signaling pathways regulating blood-tissue barriers – lesson from the testis - Wen, Qing (Biochim Biophys Acta, 2017)
Signal pathways that regulate blood-tissue barriers are important for studying the biology of various blood-tissue barriers. This information, if deciphered and better understood, will provide better therapeutic management of diseases particularly in organs that are sealed by the corresponding blood-tissue barriers from systemic circulation, such as the brain and the testis. These barriers block the access of antibiotics and/or chemotherapeutical agents across the corresponding barriers. Studies in the last decade using the blood-testis barrier (BTB) in rats have demonstrated the presence of several signaling pathways that are crucial to modulate BTB function. Herein, we critically evaluate these findings and provide hypothetical models regarding the underlying mechanisms by which these signaling molecules/pathways modulate dynamics. This information should be carefully evaluated to examine their applicability in other tissue barriers which shall benefit future functional studies in the field.